Design of frequency-tunable mesh washer isolators using shape memory alloy actuators. (May 2016) - Jeong, Ho-Kyeong; Lee, Juho; Han, Jae-Hung; Wereley, Norman M
This article introduces a novel frequency-tunable isolator that uses shape memory alloy wires as actuators and as an isolation material. The isolation material is a compressed mesh washer using the pseudoelasticity of the shape memory alloy. Frequency tuning of the isolator can easily be achieved using a simple electric circuit. Two improved models of frequency-tunable isolator, based on the authors' previous model, were proposed and fabricated. This article presents detailed design procedures for adaptive shock isolators for launch vehicles that are able to achieve both shock attenuation performance and avoidance of vibration amplification. Launch vehicles experience a severe dynamic environment during the flight phase. In particular, pyroshock generated from several separation events could result in malfunctions of electrical components. Moreover, low-frequency vibration (<100 Hz) at the maximum dynamic-pressure phase could reduce the structural integrity of payloads. With this system, the resonant frequencies of the isolators are selectively controlled in two states using an adaptive mechanical system with compression of the isolation materials. Successful designs for the isolators and various test results regarding frequency tuning are presented.